COMPARATIVE ANALYSIS OF FOSTER CARE FOR ADULTS IN REPUBLIC OF CROATIA AND REPUBLIC OF MACEDONIA - Laklija, Maja; Ilievski, Vladimir (Ревија за социјална политика/Journal of Social Policy, 2015)
The aim of this work is to show practice and opportunities for improvement of foster care for adults in Republic of Croatia and Republic of Macedonia, through a comparative analysis of the legal framework governing foster care. The analysis will focus on the comparison of certain statutory provisions that are related to foster care and state the main differences that exist in these countries. We will analyze the provisions relating to the types of foster care present in those countries, the accommodation capacities, the conditions to be met to perform foster activities, training and education of foster careers, the issuance of a license to conduct foster care and issues related with conclusion of the contract and compensation for foster carers. We will also display statistics about the current situation on the field of foster care in each country and propose guidelines for the further development of foster care for adults in Croatia and Macedonia.